Surface modification of biochar derived from gaharu waste via pyrolysis - Mohd Azmi, Mohd Darul Imran (2017)
Biochar is a solid material obtained from the carbonization of biomass. This research objective is to produce biochar derived from gaharu waste. The gaharu waste was taken from Bukit Larut, Perak. The production biochar was at 3 different temperature, 400oC, 500oC and 600oC. This research also analyzes the surface area and adsorption ability of the biochar using methylene blue. The biochar undergoes modifications using H3PO4, NaOH and hot water before the analysis was being performed. The yield of the biochar produced was 42%, 38% and 24% for 400 o C, 500 o C and 600o C respectively. The BET surface area of samples treated by H3PO4 was 2.7569, 1.8935 and 1.9578 m2 /g for pyrolysis temperature of 400, 500 and 600o C respectively. The samples modified with NaOH had the BET surface area of 16.1636 m2 /g at 400o C of pyrolysis temperature. At 500o C and 600o C, the BET surface area were 2.0799 and 1.9744 m2 /g respectively. The BET surface area of samples treated by hot water was 37.9505, 2.2321, and 1.4973 m2 /g for pyrolysis temperature of 400, 500 and 600o C respectively. The pore volume of the biochar treated with H3PO4 was 0.001668 cm3 /g at 400o C, 0.001510 cm3 /g at 500o C and 0.001825 cm3 /g at 600o C. The pore volume for samples treated with NaOH were 0.019201, 0.007659 and 0.006730 cm3 /g. The pore volume of samples treated by hot water was 0.021265, 0.005720 and 0.005788 cm3 /g at 400, 500 and 600o C respectively. Thus, NaOH is the best surface modification in increasing the porosity of the biochar. The adsorption of methylene blue for H3PO4 modification was 0.3547mg/g , 0.2678mg/g and 0.2590mg/g for 400 oC, 500 oC and 600oC respectively. For NaOH modification, the adsorption value was 0.8706mg/g for 400 oC, 0.7305mg/g for 500 oC and 0.8076mg/g for 600 oC. The adsorption of methylene blue for hot water modification was 0.8830mg/g, 0.7083mg/g and 0.7681mg/g for 400 oC, 500 oC and 600oC respectively. The optimum temperature to produce biochar was 400oC and the chemical modifications using NaOH and hot water can increase the ability of methylene blue adsorption.